IMPLEMENTASI METODE DEMONSTRASI UNTUK PENDIDIKAN KEBENCANAAN PADA KEGIATAN EKSTRAKURIKULER DI SMA - Arwi Irnawati; Muzani Jalaludin; Cahyadi Setiawan (Universitas Negeri Padang, 2023)
This study is related to the implementation that can be done for disaster education materials with demonstration methods in extracurricular activities in high school. The purpose of this study was to determine the forms of implementation of demonstration methods for disaster education in extracurricular activities at the high school level so as to provide learning and capacity building of students against disaster risk. The research method used is descriptive quantitative data collection in the form of literature. The results showed that the implementation of disaster education in extracurricular activities using the demonstration method requires several stages, namely the preparation, implementation, and evaluation. There are two extracurricular activities in high school that can be integrated with disaster education using demonstration methods, namely Scouts and PMR. Scout activities can demonstrate disaster education about mitigation efforts that must be done, as well as about the path and evacuation efforts in the event of a disaster, the manufacture of stretchers for the evacuation of disaster victims, helping victims who are at high altitudes and at low bases, such as valleys by using rope knots, and the skills of erecting emergency tents. Meanwhile, PMR activities that can demonstrate more disaster education about medical treatment to disaster victims.